PERAN BADAN USAHA MILIK DESA (BUMDes) AGUNG WILLIS DESA GOMBOLIRANG DALAM MENINGKATKAN PENDAPATAN ASLI DESA - Moh. Asadi; Ansari Ansari (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2024)
Development achievements within a community do not always depend on the availability of financial funds and financial management but are influenced by community involvement and response. This study aims to understand the role and management of Agung Willis Village-Owned Enterprises (BUMDes) Gombolirang Village in increasing village original income (PADes). This research method applies a descriptive analysis approach that emphasizes data quality. The data used in this study are descriptive. Research data can be classified into two types, namely primary data and secondary data. The method of collecting information involves observation, interviews, and the collection of documents. The results showed that the role of the Agung Willis Village-Owned Enterprise has been running well, including in running a terob rental service business and badminton building. This effort can increase the village's original income and create job opportunities for the village community. BUMDES Agung Willis continues to play an effective role in increasing the contribution of villages' original income in Gombolirang despite being affected by the decline due to the COVID-19 pandemic. Good and professional BUMDes management. The management of BUMDes Agung Willis is based on the principles of cooperation, transparency, professionalism, and independence. The net income of PADes Gombolirang Village is the result of transactions minus operational costs, taxes, obligations of other parties, and the depreciation of inventory items in one financial year.